Networking for Researchers of Vocational Education : Discovering divergence cross-culturally? - Weil, Markus [Verfasser] (My University, 2008)
"If an approach of networking within vocational education practice is to be taken seriously it must also have an impact on comparative research and on the role of researchers. Using an example from a project involving network building for European junior researchers I highlight the necessity for discovering divergence within vocational education cross-culturally. A network approach makes this comparison more authentic because it leaves the autonomy of being diverse to the involved nodes of a network without necessarily creating an artificial convergence between the different systems of education and work." (Autorenreferat, BIBB-Doku)
Keywords: L 4.2.4 Expertennetzwerke / Wissensplattformen; Berufsbildungsforschung; Netzwerk; Multikulturalität; Interdisziplinarität